The role of mosques in educating rural muslim communities to prevent the Covid-19 Pandemic - Abdul Rahman; Endang Sutisna Sulaeman; Fresthy Astrika Yunita; Hardiningsih Hardiningsih; Okta Hadi Nurcahyono (International Journal of Health Science and Technology, 2022)
Indonesia is a country with the largest Muslim population in the world, has nearly one million mosques, is used for daily and Friday collective prayers, and is thought to be at high risk of being infected with Covid-19. The essence of the problem is that the five daily prayers and Friday prayers once a week have become controversial, physical crowds are at risk of Covid-19. The theory of 'Experiential education' by John Dewey is used to explain social interactions in mosques between imams and makmum, ustadz and people, Muslim leaders and citizens. They exchanged experiences in dealing with Covid-19.. This study aims to explain the role of mosques in increasing knowledge, attitudes, and skills in preventing and overcoming the Covid-19 pandemic. The method used in this study uses a phenomenological approach.. The results of this study can be concluded that first, Friday prayers at the mosque are closed for two weeks. Second, there are three groups of crowds that occur in the mosque environment with different transmission risks between mosques. Third, the protocol  went well because of the results of the education of religious leaders and community leaders. Fourth, ablution is relevant to 3M to prevent the Covid-19. Fifth, the cohesiveness of mosque leaders and the Covid-19 cluster is a lesson for the community at the mosque and in the market. The knowledge and experience of Muslim residents following ustadz and khotib ensures the sustainability of 3M implementation in every village.